2018
DOI: 10.1002/brb3.1040
|View full text |Cite
|
Sign up to set email alerts
|

Utility of thermographic measurements of laterality of body surface temperature to prevent misdiagnosis of acute Wallenberg's syndrome

Abstract: IntroductionAcute Wallenberg's syndrome (WS) is sometimes misdiagnosed as a nonstroke disease including auditory vertigo, and careful neurological examination is required for a precise diagnosis. Lateral difference of body surface temperature (BST) had been reported as a symptom of WS, although further details of this symptom are currently lacking. Our aim was to investigate the laterality of BST of patients with acute WS using thermography and the usefulness of thermography to detect acute WS.MethodsNine cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Thermographic scan was performed at the same time points in all patients. As the laterality of BST decreased with residual sensory symptoms and time, 5,12 this study could provide more clinically important information.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Thermographic scan was performed at the same time points in all patients. As the laterality of BST decreased with residual sensory symptoms and time, 5,12 this study could provide more clinically important information.…”
Section: Discussionmentioning
confidence: 88%
“…However, one study suggests that the cause of lateralized BST in patients with WS is a disruption of the connecting pathway of sweating and skin blood flow descending from the lateral brainstem, including the ventrolateral medulla. 5 Disrupted sweating and vasoconstrictive function are likely to increase the BST in the ipsilateral to the infarction in patients with WS. Another study showed that lateralized BST in patients with WS is probably caused by damage to the medullary vasomotor centers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermography was found to be a useful tool to differentiate between pontine infarction and Wallenberg's syndrome using the body service temperature [13].…”
Section: Introductionmentioning
confidence: 99%